Evaluation of the Strength of Reinforced Concrete Beams in the Construction of Phase II Social Institution Building in Medan According to SNI 2847:2019 and SNI 1726:2019 (Case Study) - Manik, Junesra Florensya (Jurnal Mekintek : Jurnal Mekanikal, Energi, Industri, Dan Teknologi, 2024)
The construction of a multi-storey building requires a structural analysis that is also planned to be earthquake resistant. The building structure is planned using the calculation procedures for reinforced concrete structures based on SNI 2847:2019 and SNI 1726:2019. The evaluation of structural elements carried out will show how the difference in reinforcement detailing of reinforced concrete beam structural elements is evaluated based on SNI 2847:2019 and SNI 1726:2019, knowing the strength of the reinforcement in the beam installed by calculating the cross-sectional analysis of bending and shear. The evaluation was carried out on the upper structure of the Phase II Social Institution Building in Medan with a Special Moment Bearing Frame System (SRPMK). The evaluation was carried out with data collection methods, namely primary data and secondary data and data processing in the form of direct planning methods with the help of SAP 2000 V.24 software so as to obtain the results of the analysis which is the purpose of this research. The results showed that all beams have nominal moment strength that meets the requirements (ϕMn) > Mu , nominal shear strength on the beam meets the requirements Vu < ϕVn. The detailing of the installed reinforcement was carried out in the evaluation of flexural strength and shear strength calculated in accordance with SNI 2847:2019. The results also show that the deviation between levels meets the requirements of the deviation between floors of the design level (Δ) < (Δa) in accordance with SNI 1726:2019.